Pendidikan Kesehatan Personal Hygiene Saat Menstruasi pada Remaja Putri dengan Metode Peer Group - Narsih, Umi; Homsiatur Rohmatin; Agustina Widayati (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service is to provide health education about personal hygiene during menstruation to adolescent girls at MTs Darul Ulum Kraksaan-Probolinggo so that adolescent girls are able to apply personal hygiene properly during menstruation. The method used is a peer group (peer), in collaboration with the Head of MTs Darul Ulum Kraksaan. The indicator of the success of community service is that adolescent girls are able to apply personal hygiene properly during menstruation to avoid reproductive health problems. The results of community service activities inform that with the peer group method learning is fun, not boring, and casual atmosphere so that the level of understanding of adolescent girls about personal hygiene during menstruation increases to 95% and adolescent girls are able to apply personal hygiene properly during menstruation.